A Lightweight End-to-End Encryption Algorithm for IoT Data Integration: Blockchain Framework - Siddireddy, Manikumar (ProQuest Dissertations & Theses, 2024)
This thesis proposes a novel lightweight end-to-end encryption algorithm tailored for securing Internet of Things (IoT) data within a blockchain framework. With the proliferation of IoT devices generating vast amounts of sensitive data, ensuring its confidentiality and integrity during transmission and storage becomes paramount. Traditional encryption techniques may impose significant overhead on resource constrained IoT devices, hindering their efficiency and scalability. To address this challenge, this proposed algorithm strikes a balance between robust security and computational efficiency, leveraging the inherent characteristics of blockchain technology for data integrity and immutability. Through extensive experimentation and analysis, this thesis demonstrates the efficacy and feasibility of this encryption scheme in safeguarding IoT data while maintaining compatibility with blockchain frameworks. This research contributes to the advancement of secure and efficient data integration in IoT applications within distributed blockchain environments.